2016
DOI: 10.1080/15374416.2016.1220311
|View full text |Cite
|
Sign up to set email alerts
|

Harsh Parenting and Serotonin Transporter and BDNF Val66Met Polymorphisms as Predictors of Adolescent Depressive Symptoms

Abstract: Objective Depressive symptoms are prevalent and rise during adolescence. The present study is a prospective investigation of environmental and genetic factors that contribute to the growth in depressive symptoms and the frequency of heightened symptoms during adolescence. Method Participants included 206 mother-father-adolescent triads (M age at T1 = 13.06 years, SD = .51, 52% female). Harsh parenting was observationally assessed during a family conflict paradigm. DNA was extracted from saliva samples and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Both the serotonin transporter linked polymorphism ( 5‐HTTLPR ) and the brain‐derived neurotrophic factor ( BDNF ) Val66Met polymorphism were reported as moderators in the family risk‐adjustment difficulties association (Carver et al., 2011; Taylor et al., 2011). In particular, these polymorphisms seem implicated in increased risk for depression in the presence of environmental adversity (Caspi et al., 2003; Koss et al., 2018; Phillips, 2017; Valderrama & Miranda, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Both the serotonin transporter linked polymorphism ( 5‐HTTLPR ) and the brain‐derived neurotrophic factor ( BDNF ) Val66Met polymorphism were reported as moderators in the family risk‐adjustment difficulties association (Carver et al., 2011; Taylor et al., 2011). In particular, these polymorphisms seem implicated in increased risk for depression in the presence of environmental adversity (Caspi et al., 2003; Koss et al., 2018; Phillips, 2017; Valderrama & Miranda, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Relative to the BDNF Val allele, the Met allele of the polymorphism is associated with diminished BDNF protein expression in the brain (Chen et al, 2004; Egan et al, 2003). Despite some empirical inconsistencies in the identification of the BDNF gene as a moderator of environmental factors, findings from many studies have shown that socialization histories and offspring psychological functioning are heightened for Met allele carriers (Clasen, Wells, Knopik, McGeary, & Beevers, 2011; Koss, Cummings, Davies, Hetzel, & Cicchetti, 2016; Kretschmer, Vitaro, & Barker, 2014). Although the findings from these studies are commonly interpreted within diathesis-stress models, follow-up analyses directly examining the relative correspondence between the BDNF moderating findings and the diathesis-stress and differential susceptibility models are rarely conducted.…”
Section: Genetic Moderation Of the Mediational Role Of Adolescent Emomentioning
confidence: 99%